2015
DOI: 10.1186/s12890-015-0007-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a web-based asthma self-management system: a randomised controlled pilot trial

Abstract: BackgroundAsthma is the most common chronic condition of childhood and disproportionately affects inner-city minority children. Low rates of asthma preventer medication adherence is a major contributor to poor asthma control in these patients. Web-based methods have potential to improve patient knowledge and medication adherence by providing interactive patient education, monitoring of symptoms and medication use, and by facilitation of communication and teamwork among patients and health care providers. Few s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(111 citation statements)
references
References 36 publications
1
107
2
1
Order By: Relevance
“…1). Of these 16 studies, 11 (69%) reported on randomised controlled trials (RCT) (10 two-arm RCTs [50][51][52][53][54][55][56][57][58][59], one three-arm RCT [60]) and 5 (31%) were feasibility studies employing a pre-post design [61][62][63][64][65] (Multimedia Apendix 2). Two of the RCTs reported on the same intervention [51,59], however, as they reported on different outcomes, and different uses of theory, we have considered them as separate interventions.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1). Of these 16 studies, 11 (69%) reported on randomised controlled trials (RCT) (10 two-arm RCTs [50][51][52][53][54][55][56][57][58][59], one three-arm RCT [60]) and 5 (31%) were feasibility studies employing a pre-post design [61][62][63][64][65] (Multimedia Apendix 2). Two of the RCTs reported on the same intervention [51,59], however, as they reported on different outcomes, and different uses of theory, we have considered them as separate interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies measured adherence using electronic monitoring [52,60,61] while 2 used self-report [54,58]. All studies reported a significant positive effect of the intervention on adherence.…”
Section: Medication Adherencementioning
confidence: 99%
See 3 more Smart Citations